2013
DOI: 10.1063/1.4809591
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the steady engulfment regime in a three-dimensional T-mixer

Abstract: The steady engulfment regime in a fully three-dimensional micro T-mixer is investigated. This regime is of significant interest for applications since it implies high mixing between the flow streams entering the device. Direct numerical simulations are first used to characterize this regime. In particular, the main vortical structures typical of the engulfment regime and their effects on mixing are investigated. Threedimensional linear stability analysis is successively applied to the characterization of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
97
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(109 citation statements)
references
References 19 publications
(27 reference statements)
10
97
0
Order By: Relevance
“…For the case with square inlet cross-sections (i.e., with Ä i = 1), the length of the mixing channel, L o , was varied between 12.5D and 45D, in order to assess the effect of this geometrical parameters on the onset of the different flow regimes. Note that L o = 12.5D was used in previous investigations (Galletti et al, 2012;Fani et al, 2013), while L o = 25D was used in a recent work (Fani et al, 2014). Following the results of this sensitivity analysis, L o = 25D was adopted for the other two considered T-mixer configurations, i.e.…”
Section: T-mixer Geometrymentioning
confidence: 99%
See 1 more Smart Citation
“…For the case with square inlet cross-sections (i.e., with Ä i = 1), the length of the mixing channel, L o , was varied between 12.5D and 45D, in order to assess the effect of this geometrical parameters on the onset of the different flow regimes. Note that L o = 12.5D was used in previous investigations (Galletti et al, 2012;Fani et al, 2013), while L o = 25D was used in a recent work (Fani et al, 2014). Following the results of this sensitivity analysis, L o = 25D was adopted for the other two considered T-mixer configurations, i.e.…”
Section: T-mixer Geometrymentioning
confidence: 99%
“…Here, the fluid elements at the confluence of the two inlet flows reach the opposite side of the mixing channel, thus largely increasing the degree of mixing. Many studies in the literature focused on the engulfment regime, because of the significant mixing efficiency achieved in this regime (see, e.g., Lindken et al, 2006;Soleymani et al, 2008;Ooms et al, 2009;Galletti et al, 2012;Fani et al, 2013;Poole et al, 2013). Finally, a few investigations have indicated that by further increasing Re, the flow becomes first unsteady and periodic in time and eventually chaotic (Dreher et al, 2009;Kockmann and Roberge, 2011;Fani et al, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…At higher Re, the flow regains its symmetric state and the rate of mixing decreases. Recently, Fani et al (2013) studied the engulfment regime in a three-dimensional T-mixer with a quadratic cross-section by direct numerical simulation and a global stability analysis. The mechanism of engulfment was found to be the tilting of the vortical structures at the beginning of the exit channel.…”
Section: Introductionmentioning
confidence: 99%
“…The study of changing the hydrodynamic mode of the mixer operation also does not reveal a significant reserve for reducing the energy costs of the process [18]. The use of a microchannel in a mixer is expedient in the opinion technology audit and Production reserVes -№ 3/3(35), 2017 ISSN 2226-3780 of the authors only if the influence on the central part of the jet providing pulsations [19].…”
Section: Research Of Existing Solutions Of the Problemmentioning
confidence: 99%